Design And Construction Of A Thermoelectric Generator-Based Power System Utilizing Exhaust Manifold Heat And Fuel Flow As Cooling Medium - Yogie Wijaya; Setya Wijayanta; Femmy Sofie Schouten (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2026)
Internal combustion engines dissipate approximately 50 percent of the energy produced through the exhaust system, representing a significant source of untapped thermal energy. This study presents the design, construction, and experimental evaluation of a Thermoelectric Generator (TEG) based power generation system that simultaneously harnesses heat from the exhaust manifold of a four stroke gasoline motorcycle engine and utilizes circulating fuel flow as the cooling medium on the cold side of the TEG modules. Ten SP1848 TEG modules were integrated onto a custom fabricated exhaust manifold and connected in series and parallel configurations. Three fuel flow rates were investigated, namely 0.59, 0.78, and 1.44 L/min, controlled by a DC pump regulated through an adjustable potentiometer. Temperature data from both sides of each module were acquired using ten Type K thermocouples interfaced with an ESP32 microcontroller. Electrical output was measured using a calibrated watt meter with a fixed 10 ohm resistive load. Results demonstrate that the series configuration achieves superior power output, with a peak of 1.03 W at a fuel flow rate of 1.44 L/min and a maximum hot side temperature of 98.10 C. The parallel configuration, conversely, generates higher power at the lowest flow rate of 0.59 L/min with an output of 0.61 W, driven by an increased temperature difference. A positive linear relationship (R2 = 0.80) between temperature difference and output power is confirmed for the series circuit. These findings demonstrate that dual utilization of exhaust heat and fuel cooled heat exchange represents an effective and practical strategy for auxiliary power generation in conventional vehicles, offering significant implications for energy efficiency and waste heat recovery technology.